Novozelandska staroselska književnost v slovenskem prevodu - Čerče, Danica (Primerjalna književnost, 2015)
This article examines the Slovene translations of the novels The Whale Rider and Whanau II by Maori writer Witi Ihimaera. This is done from the perspective of how successfully they decipher and reconstruct cultural, historical and stylistic specificities of the source texts in the target Slovene culture, highlighting some of the translators' choices which may be avoided in the future in order to enhance the translations' role as intercultural mediators.
Keywords: Ihimaera, Witi, 1944-; "Legenda o jezdecu kitov"; "The Whale Rider"; "Ponesite me domov"; "Whanau II"; novozelandska književnost; staroselci; Maori; literarno prevajanje; prevodi v slovenščino; prevajalske strategije; podomačitev; potujitev